2015
DOI: 10.1177/1099636215577367
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the compression-after-impact behavior of foam-core sandwich panels

Abstract: This paper presents the experimental results pertaining to the deformation, failure mode, failure mechanism and residual strength for the compression-after-impact tests of woven polymer-based foam-core sandwich panels. Sandwich panels with impact-type damage, inflicted via low-velocity impact, were tested to failure in compression. The optical strain measurement system ARAMIS was used to obtain the complete nonuniform strain and displacement fields of the damaged face-sheet. Consequently, damage in the face-sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…In addition, the normalized CAI strength gradually decreased with the increasing incident impact energies. Similar findings were reported by Wang et al [50]. At an impact energy of 15 J, the normalized reductions of this strength were: 41% in the carbon/epoxy structure, 43% in the glass/epoxy structure, 60% in the Kevlar/epoxy structure, and 70% in the optimum banana/epoxy structure.…”
Section: Compression After Impact (Cai) Of Structure Propertiessupporting
confidence: 89%
“…In addition, the normalized CAI strength gradually decreased with the increasing incident impact energies. Similar findings were reported by Wang et al [50]. At an impact energy of 15 J, the normalized reductions of this strength were: 41% in the carbon/epoxy structure, 43% in the glass/epoxy structure, 60% in the Kevlar/epoxy structure, and 70% in the optimum banana/epoxy structure.…”
Section: Compression After Impact (Cai) Of Structure Propertiessupporting
confidence: 89%
“…For example, an experimental study on the indentation of PMI foam cored sandwich composites showed that PMI core density and the shape of the indenter has a great influence on the indentation response of the sandwich specimens . In another study, it was observed that the residual compressive strength of the PUF core‐based sandwich composites after the impact loading was dependent on a number of parameters such as the impact energy, core thickness, face sheet thickness and the diameter of the impactor . Within polymer cores, PUF has been undoubtedly the most thoroughly researched core material.…”
Section: Sandwich Structuresmentioning
confidence: 99%
“…Digital image correlation (DIC) on sandwich specimens is performed by Wang et al [15], using a calibrated stereo camera system monitoring a speckle pattern on the specimen face sheet surface. However, they do not conduct the DIC directly in LVI tests, but in compression after impact (CAI) tests, using specimens which were not fully penetrated during the LVI tests.…”
Section: Introductionmentioning
confidence: 99%